1998
DOI: 10.1046/j.1365-2028.1998.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tourist hunting on large mammals in Tanzania: an initial assessment

Abstract: In Tanzania, where tourist hunting is employed as a conservation tool for habitat protection, information on population sizes and hunting offtake was used to assess the impact of tourist hunting on mammal densities. In general, tourist hunting pressure was unrelated to local population sizes, but for most species, animals were removed at a level of less than 10% of the local population size, suggesting that over‐exploitation was unlikely. Eland, however, and perhaps small antelope, bushbuck, kudu and reedbuck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 0 publications
0
38
1
1
Order By: Relevance
“…Based on that, they suggest that wildlife can be protected by`prohibition of human activities backed up by on-site enforcement'. In another paper (Caro et al, 1998b) they suggest that`sustained exploitation' can be achieved by adjusting hunting quotas.…”
Section: Conclusive Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on that, they suggest that wildlife can be protected by`prohibition of human activities backed up by on-site enforcement'. In another paper (Caro et al, 1998b) they suggest that`sustained exploitation' can be achieved by adjusting hunting quotas.…”
Section: Conclusive Remarksmentioning
confidence: 99%
“…Caro et al (1998b) found that while the majority of species in Tanzania are hunted at a level that can be sustained, certain species are exploited at dangerously high levels. These are`eland, and possibly small antelope, principally duikers, bushbuck, both species of kudu and reedbuck, and perhaps lion and leopard'.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal declines are mostly related to illegal hunting, land use changes, droughts, and isolation of protected areas through fencing [18][19][20]. However, trophy hunting promotes off-takes of a supposedly small proportion of males from a population [21] and the associated impacts on population dynamics of most polygamous ungulates are expected to be minimal [22].…”
Section: Introductionmentioning
confidence: 99%
“…L'argument en faveur de la chasse au trophée consiste à dire que, lorsqu'elle est bien gérée, cette chasse peut être un outil de conservation essentiel car elle peut, notamment : i) être durable, compte tenu du faible niveau de prises (Leader- ; ii) créer des incitations en matière de conservation, surtout en encourageant l'utilisation des terres pour les espèces sauvages (Lindsey et al 2006 ; iii) générer des revenus (droits par visiteur) supérieurs à ceux du tourisme, avec l'avantage que ces revenus peuvent être générés par un plus petit nombre de personnes (Lewis & Alport 1997) et dans des zones où les alternatives comme l'écotourisme pourraient ne pas être viables, car la chasse au trophée nécessite moins d'infrastructures développées (Wilkie & Carpenter 1999, Leader-Williams & Hutton 2005 ; iv) produire un effet protecteur pour les espèces et d'autres habitats dans des sites de chasse désignés (qu'il s'agisse de concessions commerciales ou d'aires de conservation communautaires) (Lindsey et al 2009) ; et v) dissuader la chasse illégale dans les sites où la chasse au trophée est pratiquée. Les arguments s'opposant à la chasse au trophée incluent : l'impact négatif de ce type de chasse sur les effectifs des populations d'espèces sauvages, leur structure et leur adéquation (voir, par exemple, Loveridge et al 2007, Croes et al 2011, y compris concernant les espèces non ciblées ; les questions éthiques et liées au bien-être animal ; et les inquiétudes relatives à la corruption, à la participation communautaire, à la mauvaise gestion des quotas et à la distribution des revenus (voir, par exemple, Caro et al 1998, Mayaka et al 2004). …”
Section: Chasse Au Trophéeunclassified